2018
DOI: 10.15244/pjoes/75871
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Release from Poultry and Pig Housing

Abstract: The article investigates the scientific literature regarding N 2 O emissions according to housing and manure management in poultry and pig buildings. The majority of the N 2 O is emitted from manure storages and housing space, with small amounts emitted from the surface of passages. Many factors must be considered in successful emission evaluation, including season of the year, amount and depth of the bedding, animal density, type and floor space, feeding and watering practices, ventilation, temperature, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…However, N 2 O emission rates might be mostly related with the litter management (i.e., the interphase aerobic/anaerobic conditions of the litter), but litter temperature and protein content in the diet could enhance the N 2 O loss (Figure 2) [4][5][6]. Moreover, previous studies reported low N 2 O concentrations close to the detection limit levels and tended to be higher in winter than in summer, being negatively affected by the ventilation rate [4][5][6]32]. The average annual N 2 O emission rates from broiler houses with new litter material in each production cycle varied among European countries, ranging from 0 mg day −1 broiler −1 in France [25] to 2 to 6 mg day −1 broiler −1 in Portugal [4,5] and 46 mg day −1 broiler −1 in Spain [5].…”
Section: Nitrous Oxidementioning
confidence: 96%
See 2 more Smart Citations
“…However, N 2 O emission rates might be mostly related with the litter management (i.e., the interphase aerobic/anaerobic conditions of the litter), but litter temperature and protein content in the diet could enhance the N 2 O loss (Figure 2) [4][5][6]. Moreover, previous studies reported low N 2 O concentrations close to the detection limit levels and tended to be higher in winter than in summer, being negatively affected by the ventilation rate [4][5][6]32]. The average annual N 2 O emission rates from broiler houses with new litter material in each production cycle varied among European countries, ranging from 0 mg day −1 broiler −1 in France [25] to 2 to 6 mg day −1 broiler −1 in Portugal [4,5] and 46 mg day −1 broiler −1 in Spain [5].…”
Section: Nitrous Oxidementioning
confidence: 96%
“…The rate of formation and emission of N 2 O varies through time with changes in manure porosity, pH, temperature, moisture, amount of solids, N and protein content of the manure substrate (Figure 2) [32]. However, N 2 O emission rates might be mostly related with the litter management (i.e., the interphase aerobic/anaerobic conditions of the litter), but litter temperature and protein content in the diet could enhance the N 2 O loss (Figure 2) [4][5][6].…”
Section: Nitrous Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, international regulations also intend to protect birds and workers health, by limiting the exposure to NH3. The volatilization of NH3 is influenced by several factors such as temperature and relative humidity, ventilation rate and air velocity, excretion rate and litter removal schedule [6,8]. Some studies have been published concerning strategies to control and reduce NH3 volatilization in broiler housing, either by adding additives to litter material or by dietary manipulation [2,5,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrous oxide (N 2 O) is a greenhouse gas (GHG) with approximately 300 times the potential to produce a greenhouse effect than carbon dioxide (CO 2 ) it also has an extensive duration of persistence in the atmosphere, estimated to be over 100 years (Bange, 2008;IPCC, 2013;Prather et al, 2015;Schlesinger and Bernhardt, 2013;Turbiak et al, 2011). Moreover, it is currently the number one ozone depleting gas emitted by human activities (Broucek, 2018;Portmann et al, 2012;Wilson et al, 2013). The concentration of this gas in the atmosphere has increased considerably over the past few decades (Finlayson-Pitts and Pitts, 2000;Stalenga and Kawalec, 2008;Włodarczyk et al, 2002).…”
Section: Introductionmentioning
confidence: 99%